Preparation method of cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material

By introducing cerium and copper doping into the manganese dioxide-based material, the δ-MnO2 positive electrode material with microsphere morphology composed of nanosheets was synthesized by co-precipitation method, which solved the problems of structural collapse and low conductivity of existing materials during circulation, and achieved the improvement of high reversible capacity and stable performance.

CN119706948APending Publication Date: 2025-03-28NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411926797.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing manganese dioxide-based materials are prone to structural collapse, dissolution of active substances and low conductivity during the circulation process in aqueous zinc ion batteries, which seriously limit their development.

Method used

By constructing the MOF metal frame as the substrate, cerium and copper are reasonably selected as doped ions, and a cerium-copper co-doped δ-MnO2 positive electrode material with microsphere morphology composed of nanosheets was synthesized on the nanoscale by co-precipitation method.

Benefits of technology

The electronic and ionic conductivity of the material is improved, high reversible capacity and excellent cycle stability are achieved, while reducing the cost of material preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706948A_ABST
    Figure CN119706948A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, and belongs to the technical field of aqueous zinc ion batteries. The method comprises the following specific steps: dissolving a manganese source in a mixed alcohol solution to obtain a solution A; doping a copper source and a cerium source into the solution A in proportion, and dissolving after ultrasonic stirring to obtain a solution B; adding acid into the solution B, and ultrasonically stirring to obtain a solution C; and carrying out microwave hydrothermal treatment on the solution C to obtain a mixture. And cooling the mixture to room temperature, repeatedly centrifugally washing with deionized water and ethanol, drying to obtain a material A, heating and calcining the material A in a muffle furnace, and carrying out heat preservation to obtain the cerium-copper co-doped delta-MnO2 positive electrode material which is recorded as CexCuyK0. 19Mn0. 935O2. The invention also discloses a preparation method of the cerium-copper co-doped delta-MnO2 positive electrode material. The electrode material is uniform in particle size, high in crystallinity, high in reversible capacity and excellent in cycling stability, the preparation process is simple and relatively mature, and certain industrial feasibility is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to a method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material. Background Art

[0002] The innovative development of energy acquisition methods has not only greatly promoted the technological progress of the energy industry, but also brought unprecedented opportunities and challenges to the entire field. Electricity is the mainstay of modern industrial society and is widely used in heating, lighting, transportation and communications. At present, most of the electricity is still generated by burning non-renewable fossil energy. However, the excessive use of fossil energy has triggered a reserve crisis of non-renewable energy, resulting in serious environmental pollution and climate warming. This has also promoted the vigorous development of renewable energy, but the intermittent, unstable and uncontrollable electricity generated by renewable energy such as solar energy, tidal energy and wind energy is difficult to apply to fluctuating energy needs. At this time, there is an urgent need for a stable energy storage device to adjust the supply system and improve the efficiency of use.

[0003] Rechargeable secondary batteries are considered to be good candidates for large-scale energy storage devices due to their inherent high energy conversion efficiency, long cycle life, and easy maintenance. For current electrochemical energy storage devices, lithium-ion batteries still occupy a major market share. However, lithium-ion batteries still have problems such as high flammability and harmful electrolytes, high cost, poor safety, and lack of lithium resources, which greatly limit the long-term application and development of lithium-ion batteries in various fields. In view of these problems, researchers are constantly looking for alternatives and have focused their attention on aqueous zinc-ion batteries.

[0004] As a key component that restricts the cost and electrochemical performance of aqueous zinc-ion batteries, cathode materials have been rapidly studied and developed. At present, the cathode materials of aqueous zinc-ion batteries that have been developed include manganese-based materials, vanadium-based materials, Prussian blue and its analogs, organic materials, etc. Among them, Prussian blue and its analogs, and organic materials mainly have open three-dimensional framework structures, while manganese-based materials and vanadium-based materials have rich tunnels and layered structures. Manganese-based materials have great advantages in terms of economy, environmental protection, and ion transport. Among them, manganese dioxide has good electrochemical reversibility and a wide voltage window (~2.0V). At the same time, the rich tunnel structure and three-dimensional space framework of manganese dioxide are conducive to rapid ion transport and storage. The diversity of manganese dioxide's crystal structure also makes it show great advantages in multifunctional ion storage. In addition, manganese dioxide can be prepared from cheap raw materials by a simple one-step hydrothermal method, which has great prospects in large-scale production applications.

[0005] The basic crystal structure of manganese dioxide (MnO2) is a manganese atom surrounded by six oxygen atoms to form an [MnO6] octahedron. The basic octahedral [MnO6] unit is continuously connected to adjacent units in different ways by sharing vertices and edges to form various manganese dioxide polymorphs. Due to the tunable structure, excellent electrochemical performance, environmental protection and economy of manganese dioxide crystals, they have been widely used as positive electrode materials for aqueous zinc ion batteries and have a capacity of 616 mAh g when 2 electron transfer occurs. -1 High theoretical capacity.

[0006] There are many types of manganese dioxide crystal structures, and they have rich tunnel structures and large and open layered structures, more active sites, and birnessite-type manganese dioxide (δ-MnO2) has a relatively large interlayer distance. Good for Zn 2 + The insertion and extraction of -1 However, pure δ-MnO2 is usually prone to structural collapse, active material dissolution and low conductivity during the cycle process, which seriously limits its development in aqueous zinc-ion batteries. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material, aiming to overcome the limitations of existing manganese dioxide-based materials and improve the performance and cycle stability of aqueous zinc ion batteries. By constructing a MOF metal framework as a substrate, rationally selecting cerium and copper as doping ions, and using a coprecipitation method to synthesize a microsphere-shaped δ-MnO2 composed of nanosheets at the nanoscale. The obtained nanoflower particles have uniform particle size, high dispersibility and active sites, improve the electronic and ionic conductivity of the material, obtain a higher reversible capacity and excellent cycle stability, thereby reducing the material preparation cost while improving the electrochemical performance of the material.

[0008] The technical solution adopted by the present invention to solve the above technical problems is:

[0009] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0010] (1) dissolving a copper source and 2-methylimidazole in methanol, quickly mixing and vigorously stirring, allowing the mixture to stand after stirring, then filtering and washing the mixture with methanol and deionized water alternately, drying, and collecting the powder as Cu-MOF;

[0011] (2) dissolving the cerium source and 2-methylimidazole in methanol, quickly mixing and vigorously stirring, leaving the mixture to stand after stirring, then filtering and washing the mixture with methanol and deionized water alternately, drying, and collecting the powder as Ce-MOF;

[0012] (3) taking a manganese source and stirring and dissolving it in a mixed alcohol solution, and the resulting solution is recorded as solution A;

[0013] (4) Cu-MOF and Ce-MOF were mixed with solution A according to the molar ratio, dissolved after ultrasonic stirring, and the obtained solution was recorded as solution B. Then, a mixed acid was added to solution B, and the solution obtained after ultrasonic stirring was recorded as solution C;

[0014] (5) Solution C is subjected to microwave hydrothermal treatment to obtain a mixture, which is cooled to room temperature, repeatedly centrifuged and washed with deionized water and ethanol, and dried to obtain material A; material A is then calcined and kept warm in a muffle furnace to obtain a cerium-copper co-doped δ-MnO2 positive electrode material.

[0015] in:

[0016] In the step (1), the copper source is a mixture of CuSO4·5H2O, Cu(CH3CH2COO)2·H2O and CuNO3·6H2O, and the molar ratio of CuSO4·5H2O to Cu(CH3CH2COO)2·H2O and CuNO3·6H2O is (1-2.5):(0.05-0.1):1.

[0017] In the step (1), the molar ratio of the copper source to 2-methylimidazole is 1:(3-5), and the concentration of the copper source in methanol is 0.03 mol·L -1 ~0.06mol·L -1 ; The concentration of 2-methylimidazole in methanol is 0.1 mol·L -1 ~0.3mol·L -1 .

[0018] In the step (1), the copper source, 2-methylimidazole and methanol are mixed and stirred for 0.5 min to 1 min, and then allowed to stand at 20° C. to 30° C. for 12 h to 24 h.

[0019] In the step (2), the cerium source is a mixture of Ce2(SO4)3·8H2O, Ce(CH3CH2COO)3·nH2O and Ce(NO3)3·6H2O, and the molar ratio of Ce2(SO4)3·8H2O, Ce(CH3CH2COO)3·nH2O and Ce(NO3)3·6H2O is (1-2):(0.05-0.1):1.

[0020] In the step (2), the molar ratio of the cerium source to 2-methylimidazole is 1:(3-5), and the concentration of the cerium source in methanol is 0.03 mol·L -1 ~0.06mol·L -1 , the concentration of 2-methylimidazole in methanol is 0.1 mol·L -1 ~0.3mol·L -1 .

[0021] In the step (2), the cerium source, 2-methylimidazole and methanol are mixed and stirred for 0.5 min to 1 min, and then allowed to stand at 20° C. to 30° C. for 12 h to 24 h.

[0022] In the steps (1) and (2), the step of washing the mixture with methanol is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of methanol of the mixture, stirring the solution with a magnetic stirrer for 0.5 h to 1 h; after the stirring is completed, filtering with a glass frit funnel or filter paper to separate the mixture from the methanol.

[0023] In the steps (1) and (2), the step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding deionized water in an amount of 5 to 10 times the volume of the mixture, stirring the solution with a magnetic stirrer for 0.5 h to 1 h; after the stirring is completed, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0024] In the step (3), the manganese source is a mixture of KMnO4, Mn(CH3CH2COO)2 and MnSO4, and the molar ratio of KMnO4, Mn(CH3CH2COO)2 and MnSO4 is (2-3):(0.05-0.1):1.

[0025] In the step (3), the mixed alcohol solution is a mixture of H2O, CH3OH and CH3CH2OH, and the volume ratio of H2O, CH3OH and CH3CH2OH is (8-10):1:1.

[0026] In step (3), the concentration of the manganese source in the mixed alcohol is 0.05 mol·L -1 ~0.15mol·L -1 , the stirring time is 5min~15min.

[0027] In the step (4), the molar ratio of Cu-MOF to Ce-MOF is Cu-MOF:Ce-MOF=(1-3):(1-3); the concentration of Cu-MOF in solution A is 0.002 mol·L -1 ~0.007mol·L -1; The dissolution time of Cu-MOF and Ce-MOF in solution A is 10min to 30min.

[0028] In the step (4), the mixed acid is a mixture of glacial acetic acid, formic acid and propionic acid, and the volume ratio of glacial acetic acid, formic acid and propionic acid is 10:(0.5-1):(0.5-1); the volume ratio of the mixed acid to solution B is (0.1-0.3):(40-60), and the ultrasonic stirring time after mixing is 10 min to 30 min.

[0029] In the step (5), solution C is subjected to microwave hydrothermal treatment at 160° C. to 190° C. and a power of 150 kW for 1 h to 2 h.

[0030] In the step (5), the temperature-raising calcination is specifically: raising the temperature to 400° C. to 800° C. at a rate of 4° C. / min to 7° C. / min and calcining for 3 h to 5 h.

[0031] A cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material is prepared by the above preparation method, and the chemical composition of the positive electrode material is Ce x Cu y K 0.19 Mn 0.935 O2, 0.08≤x≤0.09, 0.036≤y≤0.041.

[0032] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0033] The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.3 mAh g, the first reversible specific capacity is 172.3 mAh g -1 ~194.0mAh·g -1 After 1000 cycles, the capacity retention rate reached 73.4% to 86.3%.

[0034] Compared with the prior art, the present invention has the following technical effects:

[0035] 1. The present invention adopts cerium-copper co-doped modified aqueous zinc ion battery δ-MnO2 microsphere positive electrode material, which produces a strong charge compensation effect. More oxygen vacancies greatly accelerate ion diffusion, which is conducive to ion embedding into the lattice. At the same time, since more high-valent Mn ions are replaced by co-doped M ions, the more stable MO bond enhances the stability of the δ-MnO2 skeleton.

[0036] 2. The microsphere particles composed of nanosheets synthesized by the present invention are uniform, well dispersed, and highly crystallinity, which is beneficial to improving the electrochemical performance of the material.

[0037] 3. The material obtained by the present invention is applied to aqueous zinc ion batteries, has excellent rate performance, charge and discharge performance and stable cycle life, the preparation process is simple and relatively mature, and has certain industrial feasibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 30,000 times SEM image of the δ-MnO2 cathode material obtained in Example 1 of the present invention;

[0039] Figure 2 90,000 times SEM image of the δ-MnO2 cathode material obtained in Example 1 of the present invention;

[0040] Figure 3 Cyclic performance curve of the δ-MnO2 cathode material obtained in Example 1 of the present invention;

[0041] Figure 4 This is a rate performance diagram of the δ-MnO2 positive electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] Example 1

[0043] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0044] (1) 4.2252 mmol CuSO4·5H2O, 0.0846 mmol Cu(CH3CH2COO)2·H2O, 1.6901 mmol CuNO3·6H2O and 24 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25°C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Cu-MOF.

[0045] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0046] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0047] (2) 3.45 mmol Ce2(SO4)3·8H2O, 0.15 mmol Ce(CH3CH2COO)3·nH2O, 2.4 mmol Ce(NO3)3·6H2O and 24 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25 °C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Ce-MOF.

[0048] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0049] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0050] (3) A solution of 3.702 mmol KMnO4, 1.234 mmol MnSO4, 0.064 mmol Mn(CH3CH2COO)2 and 50 mL H2O, 5 mL CH3CH2OH, and 5 mL CH3OH was stirred at 700 rpm for 15 min to prepare solution A.

[0051] (4) Solution A was ultrasonically stirred with 0.25 mmol Cu-MOF and 0.25 mmol Ce-MOF at 680 rpm for 25 min to obtain solution B. Solution B was then mixed with 0.34 mL glacial acetic acid, 0.017 mL formic acid, and 0.017 mL propionic acid and ultrasonically stirred at 700 rpm for 20 min to obtain solution C.

[0052] (5) Solution C was hydrothermaled in a microwave oven at 180°C and 150 kW for 1 h, cooled to room temperature, repeatedly washed by centrifugation with deionized water and ethanol, and dried to obtain material A; then material A was heated to 400°C in a muffle furnace at a rate of 5°C / min and calcined for 3 h to obtain a cerium-copper co-doped δ-MnO2 positive electrode material, denoted as Ce 0.084 Cu 0.038 K 0.19 Mn 0.935 O2, its 30000 times SEM image is as follows Figure 1 As shown, the 90000 times SEM image is as follows Figure 2 As shown in the figure, it can be seen that the microsphere particles composed of nanosheets synthesized in this embodiment are uniform, well dispersed and highly crystallinity.

[0053] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0054] The manganese dioxide positive electrode material of the aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 type button type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. The cycle performance curve of the positive electrode material prepared in this embodiment is shown in the figure below. Figure 3 As shown in the figure, the rate performance diagram is as follows Figure 4 As shown. At 2A·g -1 At a current density of 1.34 W, the first reversible specific capacity is 186.18 mAh g -1 After 1000 cycles, the capacity is still 155.25 mAh g -1 , the capacity retention rate reached 83.4%, showing excellent charge and discharge performance and cycle stability.

[0055] Example 2

[0056] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0057] (1) 1.79 mmol CuSO4·5H2O, 0.179 mmol Cu(CH3CH2COO)2·H2O, 1.79 mmol CuNO3·6H2O and 15 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25°C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Cu-MOF.

[0058] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0059] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0060] (2) 1.79 mmol Ce2(SO4)3·8H2O, 0.179 mmol Ce(CH3CH2COO)3·nH2O, 1.79 mmol Ce(NO3)3·6H2O and 15 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25 °C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Ce-MOF.

[0061] The steps of methanol and washing the mixture are as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture of methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0062] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0063] (3) A solution of 3.23 mmol KMnO4, 1.61 mmol MnSO4, 0.16 mmol Mn(CH3CH2COO)2 and 48 mL H2O, 6 mL CH3CH2OH, and 6 mL CH3OH was stirred at 700 rpm for 15 min to prepare solution A.

[0064] (4) Solution A was ultrasonically stirred with 0.4 mmol Cu-MOF and 0.2 mmol Ce-MOF at 680 rpm for 25 min to obtain solution B. Solution B was then mixed with 0.17 mL glacial acetic acid, 0.017 mL formic acid, and 0.017 mL propionic acid and ultrasonically stirred at 700 rpm for 20 min to obtain solution C.

[0065] (5) Solution C was hydrothermaled in a microwave oven at 160°C and 150 kW for 1.5 h, cooled to room temperature, repeatedly washed by centrifugation with deionized water and ethanol, and dried to obtain material A; material A was then heated to 700°C in a muffle furnace at a rate of 5°C / min and calcined for 4 h to obtain a cerium-copper co-doped δ-MnO2 positive electrode material, denoted as Ce 0.08 Cu 0.036 K 0.19 Mn 0.935 O2.

[0066] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0067] The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.34 mAh g, the first reversible specific capacity is 172.32 mAh g -1 After 1000 cycles, the capacity is still 148.79 mAh g -1 , the capacity retention rate reached 86.3%, showing excellent charge and discharge performance and cycle stability.

[0068] Example 3

[0069] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0070] (1) 2.875 mmol CuSO4·5H2O, 0.125 mmol Cu(CH3CH2COO)2·H2O, 2 mmol CuNO3·6H2O and 25 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25°C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Cu-MOF.

[0071] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0072] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0073] (2) 3.26 mmol Ce2(SO4)3·8H2O, 0.11 mmol Ce(CH3CH2COO)3·nH2O, 1.63 mmol Ce(NO3)3·6H2O and 25 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25 °C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Ce-MOF.

[0074] The steps of methanol and washing the mixture are as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture of methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0075] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0076] (3) A solution of 4.29 mmol KMnO4, 1.607 mmol MnSO4, 0.107 mmol Mn(CH3CH2COO)2 and 40.9 mL H2O, 4.54 mL CH3CH2OH, and 4.54 mL CH3OH was stirred at 700 rpm for 15 min to prepare solution A.

[0077] (4) Solution A was ultrasonically stirred with 0.2 mmol Cu-MOF and 0.3 mmol Ce-MOF at 680 rpm for 25 min to obtain solution B. Solution B was then mixed with 0.26 mL glacial acetic acid, 0.02 mL formic acid, and 0.02 mL propionic acid and ultrasonically stirred at 700 rpm for 20 min to obtain solution C.

[0078] (5) Solution C was hydrothermaled in a microwave oven at 170°C and 150 kW for 1.5 h, cooled to room temperature, repeatedly washed by centrifugation with deionized water and ethanol, and dried to obtain material A; then material A was heated to 600°C in a muffle furnace at a rate of 5°C / min and calcined for 3.5 h to obtain a cerium-copper co-doped δ-MnO2 positive electrode material, denoted as Ce 0.085 Cu 0.039 K 0.19 Mn 0.935 O2.

[0079] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0080] The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.34 W, the first reversible specific capacity is 180.02 mAh g -1 After 1000 cycles, the capacity is still 151.25 mAh g -1 , the capacity retention rate reached 84%, showing excellent charge and discharge performance and cycle stability.

[0081] Example 4

[0082] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0083] (1) 3.2 mmol CuSO4·5H2O, 0.25 mmol Cu(CH3CH2COO)2·H2O, 2.55 mmol CuNO3·6H2O and 30 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25°C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Cu-MOF.

[0084] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0085] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0086] (2) 3.3 mmol Ce2(SO4)3·8H2O, 0.2 mmol Ce(CH3CH2COO)3·nH2O, 2.5 mmol Ce(NO3)3·6H2O and 30 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25 °C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Ce-MOF.

[0087] The steps of methanol and washing the mixture are as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture of methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0088] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0089] (3) A solution of 3.5 mmol KMnO4, 1.496 mmol MnSO4, 0.104 mmol Mn(CH3CH2COO)2 and 40 mL H2O, 5 mL CH3CH2OH, and 5 mL CH3OH was stirred at 700 rpm for 15 min to prepare solution A.

[0090] (4) Solution A was ultrasonically stirred with 0.167 mmol Cu-MOF and 0.333 mmol Ce-MOF at 680 rpm for 25 min to obtain solution B. Solution B was then mixed with 0.17 mL glacial acetic acid, 0.015 mL formic acid, and 0.015 mL propionic acid and ultrasonically stirred at 700 rpm for 20 min to obtain solution C.

[0091] (5) Solution C was hydrothermaled in a microwave oven at 190°C and 150 kW for 1.6 h, cooled to room temperature, repeatedly washed by centrifugation with deionized water and ethanol, and dried to obtain material A; then material A was heated to 550°C in a muffle furnace at a rate of 5°C / min and calcined for 3 h to obtain a cerium-copper co-doped δ-MnO2 positive electrode material, denoted as Ce 0.09 Cu 0.041 K 0.19 Mn 0.935 O2.

[0092] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0093] The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.34 W, the first reversible specific capacity is 194 mAh g -1 After 1000 cycles, the capacity is still 142.5 mAh g -1 , the capacity retention rate reached 73.45%, showing excellent charge and discharge performance and cycle stability.

[0094] Example 5

[0095] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0096] (1) 1.85 mmol CuSO4·5H2O, 0.09 mmol Cu(CH3CH2COO)2·H2O, 1.1 mmol CuNO3·6H2O and 10 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25°C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Cu-MOF.

[0097] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0098] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0099] (2) 1.5 mmol Ce2(SO4)3·8H2O, 0.09 mmol Ce(CH3CH2COO)3·nH2O, 1.5 mmol Ce(NO3)3·6H2O and 10 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25 °C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Ce-MOF.

[0100] The steps of methanol and washing the mixture are as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture of methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0101] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0102] (3) A solution of 3.6 mmol KMnO4, 1.33 mmol MnSO4, 0.07 mmol Mn(CH3CH2COO)2 and 40 mL H2O, 5 mL CH3CH2OH, and 5 mL CH3OH was stirred at 700 rpm for 15 min to prepare solution A.

[0103] (4) Solution A was ultrasonically stirred with 0.333 mmol Cu-MOF and 0.167 mmol Ce-MOF at 680 rpm for 25 min to obtain solution B. Solution B was then mixed with 0.18 mL glacial acetic acid, 0.01 mL formic acid, and 0.01 mL propionic acid and ultrasonically stirred at 700 rpm for 20 min to obtain solution C.

[0104] (5) Solution C was hydrothermaled in a microwave oven at 165°C and 150 kW for 1.5 h, cooled to room temperature, repeatedly washed by centrifugation with deionized water and ethanol, and dried to obtain material A; then material A was heated to 600°C in a muffle furnace at a rate of 5°C / min and calcined for 3.5 h to obtain a cerium-copper co-doped δ-MnO2 positive electrode material, denoted as Ce 0.083 Cu 0.037 K 0.19 Mn 0.935 O2.

[0105] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0106] The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.3 mAh g -1 After 1000 cycles, the capacity is still 153.01 mAh g -1 , the capacity retention rate reached 84.5%, showing excellent charge and discharge performance and cycle stability.

[0107] Example 6

[0108] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0109] (1) 2.56 mmol CuSO4·5H2O, 0.08 mmol Cu(CH3CH2COO)2·H2O, 1.36 mmol CuNO3·6H2O and 20 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25°C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Cu-MOF.

[0110] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0111] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0112] (2) 2.2 mmol Ce2(SO4)3·8H2O, 0.1 mmol Ce(CH3CH2COO)3·nH2O, 1.7 mmol Ce(NO3)3·6H2O and 20 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25 °C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Ce-MOF.

[0113] The steps of methanol and washing the mixture are as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture of methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0114] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0115] (3) A solution of 4.15 mmol KMnO4, 1.7 mmol MnSO4, 0.15 mmol Mn(CH3CH2COO)2 and 41 mL H2O, 4.5 mL CH3CH2OH, and 4.5 mL CH3OH was stirred at 700 rpm for 15 min to prepare solution A.

[0116] (4) Solution A was ultrasonically stirred with 0.1 mmol Cu-MOF and 0.3 mmol Ce-MOF at 680 rpm for 25 min to obtain solution B. Solution B was then mixed with 0.275 mL glacial acetic acid, 0.0275 mL formic acid, and 0.0275 mL propionic acid and ultrasonically stirred at 700 rpm for 20 min to obtain solution C.

[0117] (5) Solution C was hydrothermaled by microwave at 180°C and 150 kW for 1.5 h, cooled to room temperature, repeatedly washed by centrifugation with deionized water and ethanol, and dried to obtain material A; then material A was heated to 450°C in a muffle furnace at a rate of 5°C / min and calcined for 4 h to obtain a cerium-copper co-doped δ-MnO2 positive electrode material, denoted as Ce 0.081 Cu 0.04 K 0.19 Mn 0.935 O2.

[0118] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0119] The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.34 Å, the first reversible specific capacity is 183.18 mAh g -1 After 1000 cycles, the capacity is still 142.3 mAh g -1 , the capacity retention rate reached 77.68%, showing excellent charge and discharge performance and cycle stability.

[0120] Example 7

[0121] A method for preparing a cerium-copper co-doped delta-MnO2 microsphere aqueous zinc ion battery positive electrode material, specifically comprising the following steps:

[0122] (1) 3.696 mmol CuSO4·5H2O, 0.112 mmol Cu(CH3CH2COO)2·H2O, 1.792 mmol CuNO3·6H2O and 28 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25°C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Cu-MOF.

[0123] The step of washing the mixture with methanol is as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0124] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0125] (2) 3.08 mmol Ce2(SO4)3·8H2O, 0.14 mmol Ce(CH3CH2COO)3·nH2O, 2.38 mmol Ce(NO3)3·6H2O and 28 mmol 2-methylimidazole were dissolved in 100 mL methanol, mixed rapidly and stirred vigorously for 0.5 min. After stirring, the mixture was allowed to stand at 25 °C for 24 h. The mixture was washed by alternating filtration with methanol and deionized water, dried, and the powder was collected as Ce-MOF.

[0126] The steps of methanol and washing the mixture are as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture of methanol, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and filtering the mixture with a glass sand core funnel or filter paper to separate the mixture from the methanol after the stirring is completed.

[0127] The step of washing the mixture with deionized water is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of the mixture with deionized water, stirring the solution with a magnetic stirrer for 0.5 to 1 hour, and after stirring, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

[0128] (3) A solution of 3.3 mmol KMnO4, 1.6 mmol MnSO4, 0.1 mmol Mn(CH3CH2COO)2 and 41.5 mL H2O, 4.25 mL CH3CH2OH, and 4.25 mL CH3OH was stirred at 700 rpm for 15 min to prepare solution A.

[0129] (4) Solution A was ultrasonically stirred with 0.3 mmol Cu-MOF and 0.1 mmol Ce-MOF at 680 rpm for 25 min to obtain solution B. Solution B was then mixed with 0.32 mL glacial acetic acid, 0.02 mL formic acid, and 0.02 mL propionic acid and ultrasonically stirred at 700 rpm for 20 min to obtain solution C.

[0130] (5) Solution C was hydrothermaled in a microwave oven at 170°C and 150 kW for 2 h, cooled to room temperature, repeatedly washed by centrifugation with deionized water and ethanol, and dried to obtain material A; then material A was heated to 600°C in a muffle furnace at a rate of 5°C / min and calcined for 4.5 h to obtain a cerium-copper co-doped δ-MnO2 positive electrode material, denoted as Ce 0.084 Cu 0.041 K 0.19 Mn 0.935 O2.

[0131] The application of the above-mentioned cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material comprises the following steps:

[0132] The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.34 mAh g, the first reversible specific capacity is 179.32 mAh g -1 After 1000 cycles, the capacity is still 154.21 mAh g -1 , the capacity retention rate reached 86%, showing excellent charge and discharge performance and cycle stability.

[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material, characterized in that: The specific steps include: (1) dissolving a copper source and 2-methylimidazole in methanol, quickly mixing and vigorously stirring, allowing the mixture to stand after stirring, then filtering and washing the mixture with methanol and deionized water alternately, drying, and collecting the powder as Cu-MOF; (2) dissolving the cerium source and 2-methylimidazole in methanol, quickly mixing and vigorously stirring, leaving the mixture to stand after stirring, then filtering and washing the mixture with methanol and deionized water alternately, drying, and collecting the powder as Ce-MOF; (3) taking a manganese source and stirring and dissolving it in a mixed alcohol solution, and the resulting solution is recorded as solution A; (4) Cu-MOF and Ce-MOF were mixed with solution A according to the molar ratio, dissolved after ultrasonic stirring, and the obtained solution was recorded as solution B. Then, a mixed acid was added to solution B, and the solution obtained after ultrasonic stirring was recorded as solution C; (5) Solution C is subjected to microwave hydrothermal treatment to obtain a mixture, which is cooled to room temperature, repeatedly centrifuged and washed with deionized water and ethanol, and dried to obtain material A; material A is then calcined and kept warm in a muffle furnace to obtain a cerium-copper co-doped δ-MnO2 positive electrode material.

2. The method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In the step (1), the copper source is a mixture of CuSO4·5H2O, Cu(CH3CH2COO)2·H2O and CuNO3·6H2O, and the molar ratio of CuSO4·5H2O to Cu(CH3CH2COO)2·H2O and CuNO3·6H2O is (1-2.5):(0.05-0.1):1; The molar ratio of the copper source to 2-methylimidazole is 1:(3-5), and the concentration of the copper source in methanol is 0.03 mol·L -1 ~0.06mol·L -1 ; The concentration of 2-methylimidazole in methanol is 0.1 mol·L -1 ~0.3mol·L -1 The copper source, 2-methylimidazole and methanol are mixed and stirred for 0.5 min to 1 min, and then allowed to stand at 20°C to 30°C for 12h to 24h.

3. The method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In the step (2), the cerium source is a mixture of Ce2(SO4)3·8H2O, Ce(CH3CH2COO)3·nH2O and Ce(NO3)3·6H2O, and the molar ratio of Ce2(SO4)3·8H2O, Ce(CH3CH2COO)3·nH2O and Ce(NO3)3·6H2O is (1-2):(0.05-0.1):1; The molar ratio of the cerium source to 2-methylimidazole is 1:(3-5), and the concentration of the cerium source in methanol is 0.03 mol·L -1 ~0.06mol·L -1 , the concentration of 2-methylimidazole in methanol is 0.1 mol·L -1 ~0.3mol·L -1 The cerium source, 2-methylimidazole and methanol are mixed and stirred for 0.5 min to 1 min, and then allowed to stand at 20°C to 30°C for 12h to 24h.

4. The method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In the steps (1) and (2), the step of washing the mixture with methanol is specifically as follows: transferring the mixture to a suitable beaker, adding 5 to 10 times the volume of methanol of the mixture, stirring the solution with a magnetic stirrer for 0.5 h to 1 h; after the stirring is completed, filtering with a glass sand core funnel or filter paper to separate the mixture from the methanol; The steps of washing the mixture with deionized water are specifically as follows: transferring the mixture to a suitable beaker, adding deionized water 5 to 10 times the volume of the mixture, stirring the solution with a magnetic stirrer for 0.5 h to 1 h; after the stirring is completed, filtering with a glass sand core funnel or filter paper to separate the mixture from the deionized water.

5. The method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In the step (3), the manganese source is a mixture of KMnO4, Mn(CH3CH2COO)2 and MnSO4, and the molar ratio of KMnO4, Mn(CH3CH2COO)2 and MnSO4 is (2-3): (0.05-0.1): 1; The mixed alcohol solution is a mixture of H2O, CH3OH and CH3CH2OH, and the volume ratio of H2O, CH3OH and CH3CH2OH is (8-10):1:1; The concentration of the manganese source in the mixed alcohol is 0.05 mol·L -1 ~0.15mol·L -1 , the stirring time is 5min~15min.

6. The method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In the step (4), the molar ratio of Cu-MOF to Ce-MOF is Cu-MOF:Ce-MOF=(1-3):(1-3); the concentration of Cu-MOF in solution A is 0.002 mol·L -1 ~0.007mol·L -1 ; The dissolution time of Cu-MOF and Ce-MOF in solution A is 10min to 30min; The mixed acid is a mixture of glacial acetic acid, formic acid and propionic acid, the volume ratio of glacial acetic acid, formic acid and propionic acid is 10:(0.5-1):(0.5-1); the volume ratio of the mixed acid to solution B is (0.1-0.3):(40-60), and the ultrasonic stirring time after mixing is 10min-30min.

7. The method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In the step (5), solution C is subjected to microwave hydrothermal treatment at 160° C. to 190° C. and a power of 150 kW for 1 h to 2 h.

8. The method for preparing a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: In the step (5), the temperature-raising calcination is specifically: raising the temperature to 400° C. to 800° C. at a rate of 4° C. / min to 7° C. / min and calcining for 3 h to 5 h.

9. A cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical composition of the positive electrode material is Ce x Cu y K 0.19 Mn 0.935 O2, 0.08≤x≤0.09, 0.036≤y≤0.

041.

10. The use of a cerium-copper co-doped δ-MnO2 microsphere aqueous zinc ion battery positive electrode material as claimed in claim 9, characterized in that: The following steps are involved: The manganese dioxide positive electrode material of aqueous zinc ion battery obtained in the above steps was used as the research electrode, and the metal zinc sheet was used as the counter electrode to assemble a CR2025 button-type aqueous zinc ion battery. The charge and discharge cycle test was carried out in the potential range of 0.8V to 1.8V. -1 At a current density of 1.3 mAh g, the first reversible specific capacity is 172.3 mAh g -1 ~194.0mAh·g -1 After 1000 cycles, the capacity retention rate reached 73.4% to 86.3%.

Citation Information

Cited By

  • Modified layered manganese dioxide cathode active material, its preparation and application in aqueous zinc-ion batteries

    CN120097389B

  • High-entropy doped manganous oxide / metal solid solution heterojunction, preparation method thereof, electrode plate and zinc ion battery

    CN120341390A

  • Lanthanum-doped manganese dioxide nanowire material as well as preparation method and application thereof

    CN122102214A

  • Ce-alpha-MnO2 / CNTs nanowire and preparation method and application thereof, aqueous zinc ion battery positive plate and preparation method thereof, and aqueous zinc ion battery

    CN122276842A